FEMINIST ACCOUNTING AND THE NARRATIVE OF STATE FISCAL ACCOUNTABILITY - Fityan Halid; Niswatin; Tri Handayani Amaliah (Pena Cendekia Insani, 2026)
This research aims to analyze how fiscal accountability is constructed in budget narratives from a feminist accounting perspective. The research uses qualitative content analysis with a critical paradigm applied to the narrative text of the 2023-2025 State Budget Financial Notes. The analysis is conducted using the directed content analysis framework derived from feminist accounting and critical accounting theories. The research findings indicate that fiscal accountability is predominantly framed by a masculine fiscal rationality that emphasizes efficiency, stability, and economic growth. Technocratic language and procedural compliance serve as legitimizing mechanisms that reinforce the centralization of state control. In this framing, women's care work and contributions experience structural invisibility, while the care dimension is reduced to output-based sectoral programs. This research expands the theoretical understanding that fiscal accountability is not value-neutral, but rather shaped by power relations and specific measurement logics. In terms of policy, these findings indicate the need for a shift toward fiscal accountability that is more relational and sensitive to care and social justice. The novelty of this research lies in its critical reading of the state budget narrative as an accounting practice that both reproduces and limits the meaning of fiscal accountability.